Back Cover: Supramolecular Recognition Influences Magnetism in [X@HVIV8VV14O54]6− Self‐Assemblies with Symmetry‐Breaking Guest Anions (Chem. Eur. J. 6/2015). Issue 6 (2nd February 2015) - Yu. Monakhov, Kirill; Linnenberg, Oliver; Kozłowski, Piotr; van Leusen, Jan; Besson, Claire; Secker, Tim; Ellern, Arkady; López, Xavier; Poblet, Josep M.; Kögerler, Paul
<x xml:space="preserve">Abstract</x> A rare case of supramolecular magnetism is observed in {V22O54(X)}‐type mixed‐valence polyoxovanadate(IV/V) host–guest systems. Here diamagnetic anionic guest species, although only in weak electrostatic contact with the surrounding polyoxovanadate host shell, strongly affect the V(3d) spin density distribution and magnetic coupling. For more details, see the Full Paper by K. Yu. Monakhov, P. Kögerler, and co‐workers on page 2387 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>